Aplikasi POC Urin Sapi pada Padi SRI di Jorong Ganting Taram - Nelson Tat Elita; Muflihayati; Fri Maulina; Wiwik Hardaningsih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Jorong Ganting Taram farmers cultivating rice using conventional systems, production is still low, namely ± 4.5 tons h-1 . The Ganting Malay Farmers Group is a pioneer to change the SRI method of rice cultivation with cow urine POC technology with EM4 activator and indigenous microbes. The purpose of implementing this community service is to increase rice production at a lower cost so as to increase yields and farmers' opinions. Activities are carried out in three ways: a) Socialization and Counseling, b). Training to make cow urine POC, c) SRI method rice demonstration plot with cow urine POC. The results of the socialization and extension of rice using the SRI and POC methods of cow urine with EM4 activator and indigenous microbes gave good value to the understanding of the material and the ability to implement. The training on making cow urine POC and applied to the rice demonstration plot using the SRI method increased the growth and yield of rice compared to the conventional system. Conclusion: SRI method of rice cultivation with cow urine POC technology increases rice yields and farmers' income.